Towards harmonization of Shari'ah screening framework - Abedeen, Zafar (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2013)
Shari'ah screening is a methodology to screen out stocks and build Shari 'ah compliant indexes. However, currently Shari 'ah index providers are employing different kind of screening criteria which seems to be hampering the headway of the industry and, subsequently, hindering the globalization of Islaruic equity market. Therefore, this research aspires to investigate the differences and similarities in the Shari 'ah screening norms of the five leading Shari 'ah indices namely Dow Jones lslaruic Market Indexes, Financial Times Stock Exchange Shari 'ah Global Equity Index Series, Securities Commission Malaysia, Standard and Poor Shari 'ah Indices and Morgan Stanly Capital International Global Islaruic Indices and aims to propose framework to harmonize those differed criteria. Qualitative methodology is employed to carry out this research. The interview is also conducted using Delphi techuique with the panel of scholars and practitioners after identifying the disparity in the Shari 'ah screening norms from the literature available. The findings suggest that the there is an urgent need to harmonize Shari 'ah screening norms in order to facilitate cross-border investments. The study finds that the decision to include weapon and media industry should be left with the respective Shari 'ah body due to their subjectivity. The companies involved in human engineering should not be incorporated in Shari 'ah-compliant investments. Mas/aha aspect of a company may be taken into account during screening. The benchmark for cash compliance should be 33% and market capitalization and total asset should be employed for computing Shari 'ah index. It also urges to conduct Shari 'ah screening operation annually. Furthermore, the study proposes the precise framewmk to attain harmonization. In addition, it is anticipated that the undertaken research should pave the way towards harmonization of Shari 'ah screening. Finally, based on the findings, the researcher recommends carrying out future research on the methodology of purification.